The Influence Of Foreign Direct Investment On The Management Of Resource Economics In Indonesia - Rijal, Syamsu; Sangkala, Masnawaty; Sahade, Sahade (Jurnal Mamangan, 2023)
Foreign Direct Investment, or FDI, plays a significant role in Indonesia’s economic growth, especially in highly strategic sectors that rely on natural resources. The purpose of this study is to examine how foreign direct investment (FDI) influences the management of the resource economy in Indonesia. The method used is qualitative, using literature studies and analyzing policy reports, scientific journals, and official data from government agencies and international organizations. Research shows that foreign investment drives economic growth and infrastructure development. But foreign investment also raises many problems, such as environmental exploitation. Strong regulation, policy transparency, and the capacity of regulatory institutions are essential for the successful management of FDI. Consequently, to deal with global investment flows, a fair, sustainable, and national interest-oriented governance approach is needed.